Pengaruh Kompetensi Guru dan Motivasi Belajar terhadap Prestasi Belajar Siswa SDN Gugus 1 Bumi Nikel Bahodopi Morowali - Armin Mohamad Ali; Loren Kaluge; Sudi Dul Aji (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2022)
Teachers must have several competencies including teaching, personality, professional, and social. The application of teacher competence can be seen from the teacher's work. The competence possessed by a teacher is reflected in the achievement of learning outcomes which are realized in the form of values ​​that describe the learning achievements of their students. In addition, student learning motivation also has an important role in student learning outcomes. The main objective of this study was to identify and analyze the influence of teacher competence and motivation on student achievement at SDN Gugus 1 Bumi Nickel Bahodopi Morowali. This study uses a quantitative approach with a correlational survey. The research population was students of class V Cluster 1 Bumi Nickel Morowali, totaling 597 students, so the sampling technique in this study used purposive sampling. The research instrument was a questionnaire and data analysis used multiple linear regression which was completed with the help of the SPSS 16 for Windows computer program. Based on the results of data analysis, teacher competence has no effect on student achievement with a significance value of 0.520, so p > 0.05. Learning motivation has no effect on student achievement with a significance value of 0.241, so that p> 0.05.